Correction: Akbar et al. Seismic Response Compression of Various MSE Walls Based on 3D Modeling. Buildings 2023, 13, 2773 - Muhammad Akbar; Huali Pan; Guoqiang Ou; Georgios Nikitas; Bilal Ahmed (Buildings)
In the published publication [...]